Zachęta do ucieczki podczas prześladowań (Mt 10, 23a) w interpretacji patrystycznej - Nieścior, Leon (Vox Patrum, 2016)
The recommendation of escape during the persecution, given by Jesus in Matth 10:23, impelled the ancient commentators to deeper reflection. Apart from the realities of the Christian life threatened by persecution, the views of the montanists rejecting the possibility of escape provoked discussion on this issue. The author of the paper has presented the thought of the Greek and Latin Fathers on this mentioned words of Jesus. The patristic reflection on Matth 10:23 points out, first of all, the reasons for fair act of fleeing. The sources allow us to enumerate the following reasons for fleeing a persecution: 1) a formal obedience to the recommendation of Jesus; 2) the decree of Divine Providence dictating and allowing escape; 3) the attitude of Christ who himself has taken similar opportunity; 4) a respect for human weaknesses that can make someone for various reasons indisposed to martyrdom; 5) a prudence ordering flee in expectation of higher losses than profits incurred by the remaining at home; 6) the trust in God providing a natural way of rescue, without „forcing” Him to the extraordinary help; 7) an urgent missionary and pastoral ministry to perform; 8) to avoid provoking persecutor to evil by own presence; 9) a specific witness of renunciation and sacrifice by leaving own home and possession; 10) the escape understood in the spiritual sense is a secession from the evil and sin. Several authors stand out in the extent and the depth of reflexion about it: Origen, Tertullian, Jerome and Augustine. The authors of 4th Century and the later could be influenced by Cyprian of Carthage. Accused by his opponents, especially novatians, he justifies theologically the escape and validates it by the later attitude: as a carefull shepherd and fearless martyr.